An Overview of Chronic Spinal Pain: Revisiting Diagnostic Categories and Exploring an Evolving Role for Neurostimulation. (15th July 2017) - Sharan, Ashwini; Riley, Jonathan; Hoelscher, Christian
Abstract : Study Design: Topic overview. Objective: To describe the varied etiologies resulting in chronic spinal pain and review the current available evidence for treatments. Summary of Background Data: Chronic pain conditions, especially those that affect the axial back and radiate to the extremities, affect a large population. This results in pronounced disability and a high socioeconomic burden. Our understanding of the underlying mechanisms for chronic pain is limited. This prevents a comprehensive diagnostic approach. Evidence from high-level clinical trials supporting treatments for chronic spinal pain is also limited. Methods: Articles were identified through PubMed searches or already known to the author. The literature was reviewed and summarized, indicating the strength of evidence available for many treatment modalities. Results: There are very few studies published that evaluate behavioral modifications for chronic spinal pain and only one long-term study investigating chronic pharmacological treatments. The data on the success of spinal surgeries to relieve chronic spinal pain suggest an unacceptably high failure rate. The best evidence (Level I) currently available suggests that spinal cord stimulation is a safe, effective, and durable treatment for chronic spinal pain. Recent clinical data support further investigation of new innovations and earlier therapeutic consideration of currently employed approaches. Conclusion: Currently, physicians are limited in the practice of evidence-based medicine regarding chronic spinal pain treatments due to both the paucity of data available and an inconsistent diagnostic nomenclature. The introduction of new neurostimulation modalities is promising but requires better characterization through ongoing prospective clinical investigation. Level of Evidence: 5